Influence of cyclic heating on physical property and biocompatibility of α- and β-form gutta-percha - Ya-An Cheng (Journal of the Formosan Medical Association, 2014)
Thermoplasticized techniques with high temperature and repetitive heating in root canal filling may cause degeneration of gutta-percha, producing cytotoxic byproducts and interfering sealing quality. This study was conducted to investigate the influence of cyclic heating on the physical property and biocompatibility of α- and β-form gutta-perchas. Methods: Both α- and β-form gutta-perchas were submitted to two heating processes: continuous heating and cyclic heating. Continuous heating was carried out by heating the samples up to 300°C and 400°C. The samples were then analyzed by differential scanning calorimetry, differential thermal analysis (DTA), and thermogravimetry. For cyclic heating process, samples were heated from 30°C to 200°C for seven cycles and analyzed with DTA and thermogravimetry. For cell adhesion assay, samples were treated (30°C to 200°C, one and seven cycles), submitted to cell culture and examined by scanning electron microscope. Results: Differential scanning calorimetry and DTA indicated that α-form gutta-percha presented a major endothermic peak at 50–57°C, while β-form gutta-percha showed two major endothermic peaks at 46–50°C and 60–63°C. Total weight loss of β-form gutta-percha was about 2-fold greater than that of α-form gutta-percha after continuous heating up to 300°C, or cyclic heating for seven times. Scanning electron microscopy showed no obvious difference of cell adhesion on α- and β-form samples, even with seven cyclic heating or one heating cycle. However, the attachment of the cells to the culture plate (the control) is better than to the gutta-percha samples. Conclusion: The increase of heating cycles for α- and β-form gutta-percha exerts no adverse influence on their biocompatibility. Because the physical property of β-form gutta-percha becomes unstable when it is heated at over 300°C or subjected to cyclic heating, β-form gutta-percha may not be recommended for use in thermoplasticized gutta-percha techniques.